GUGATAN CLASS ACTION SEBAGAI IMPLIKASI DARI PENEGAKAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - ESRA STEPHANI; NINGRUM NATASYA SIRAIT; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
Enforcement developments Law No. 5 of 1999 which interesting now is the birth of KPPU decision contains consumers loss, so that implicates consumer protection, look at the class action lawsuits in some regions in Indonesia, example KPPU Decision No. 07/KPPU-L/2007 and KPPU Decision No. 03/KPPU-L/2008. The issues to be examined in this research is about rule of class action lawsuit in the laws and regulations in Indonesia, the enforcement of Law No. 5 of 1999 and the decisions of KPPU which may have implications for class action lawsuits. Writing method used to compile this paper is the normative legal research or library research, by collecting material from books, magazines, papers, internet, legislation and other scholarly writings which closely related with the intent and purpose of the preparation of this paper. The results of this paper it can be concluded that, the KPPU decision could have implications for class action if there is an element consumer loss listed in the consideration and decision of KPPU as the initial evidence of consumer loss. Suggestions for this research is that we need to make a law about the class action as enforcement implications Law No. 5 of 1999. Kata Kunci : Implikasi, Putusan KPPU, gugatan class action